2013
DOI: 10.3390/rs5010238
|View full text |Cite
|
Sign up to set email alerts
|

Snow Grain-Size Estimation Using Hyperion Imagery in a Typical Area of the Heihe River Basin, China

Abstract: It is difficult and time consuming to use traditional measurement methods to estimate the physical properties of snow. However, the emergence of hyperspectral imagery for estimating the physical properties of snow provides a powerful tool. Snow albedo, grain size, and temperature are important factors for evaluating the surface energy balance. Using the spectrum-reflection curves of the different grain sizes of snow measured in the fields of the Binggou watershed of the Heihe River Basin, China, we analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The classification of Hyperion data using the SVM algorithm provides satisfying results for the classes snow and bare ice (user's accuracies of 90 and 70 %), confirming the successful use of Hyperion for snow and ice monitoring (Bindschadler and Choi, 2003;Casey et al, 2012;Doggett et al, 2006;Negi et al, 2013;Zhao et al, 2013). For other land cover classes (e.g., rocks and debris cover), a lower user's accuracy was obtained (60-70 %), probably due to both the coarse spatial resolution (30 m) of Hyperion for mapping these classes and the spectral similarity between the two classes.…”
Section: Discussionmentioning
confidence: 64%
“…The classification of Hyperion data using the SVM algorithm provides satisfying results for the classes snow and bare ice (user's accuracies of 90 and 70 %), confirming the successful use of Hyperion for snow and ice monitoring (Bindschadler and Choi, 2003;Casey et al, 2012;Doggett et al, 2006;Negi et al, 2013;Zhao et al, 2013). For other land cover classes (e.g., rocks and debris cover), a lower user's accuracy was obtained (60-70 %), probably due to both the coarse spatial resolution (30 m) of Hyperion for mapping these classes and the spectral similarity between the two classes.…”
Section: Discussionmentioning
confidence: 64%
“…Zhao et al () observed the relationship between the snow grain size and reflectance at 1,033 nm and the results indicated fair linear and exponential relationships between snow reflectance and snow grain size. The correlation coefficients (R) of the two models were 0.81 and 0.84, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Snow is an important constituent of the mountain cryosphere and a critical component in high mountain hydrology. As snow could cause natural hazards like snow avalanches, it has remained a subject of the longstanding monitoring program in alpine regions around the globe (Sibandze, Mhangara, Odindi, & Kganyago, 2014;Zhao, Jiang, & Wang, 2013). Snow cover dynamics has a significant effect upon the high-altitude Himalayan climate as well (Immerzeel, Droogers, de Jong, & Bierkens, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Successful applications with imaging spectroscopy data cover all environments, including the analysis of managed forests [5,6], agricultural areas [7][8][9], mining sites [10,11], urban areas [12][13][14], of unmanaged forests [15,16] and (quasi-)natural ecosystems [17][18][19], including deserts [20,21] or snow and ice [22,23], as well as inland waters and oceans [24,25]. Given the broad range of applications, a great variety of analysis approaches is used with imaging spectroscopy data, e.g., mapping and monitoring [26,27], empirical modeling [5,28,29] or physical-based modeling, especially with radiative transfer models [6,30,31].…”
Section: Introductionmentioning
confidence: 99%